2019
DOI: 10.1038/s41598-018-37239-6
|View full text |Cite
|
Sign up to set email alerts
|

Acetaldehyde forms covalent GG intrastrand crosslinks in DNA

Abstract: Carcinogens often generate mutable DNA lesions that contribute to cancer and aging. However, the chemical structure of tumorigenic DNA lesions formed by acetaldehyde remains unknown, although it has long been considered an environmental mutagen in alcohol, tobacco, and food. Here, we identify an aldehyde-induced DNA lesion, forming an intrastrand crosslink between adjacent guanine bases, but not in single guanine bases or in other combinations of nucleotides. The GG intrastrand crosslink exists in equilibrium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…We could not determine the damaged site in the oligonucleotide sequence ( Fig. 2a), suggesting the chemical instability of the lesions as previously reported [14].…”
Section: Nucleolytic Activity On Acetaldehyde-induced Dna Lesionssupporting
confidence: 43%
See 3 more Smart Citations
“…We could not determine the damaged site in the oligonucleotide sequence ( Fig. 2a), suggesting the chemical instability of the lesions as previously reported [14].…”
Section: Nucleolytic Activity On Acetaldehyde-induced Dna Lesionssupporting
confidence: 43%
“…Previously, we reported that acetaldehyde reacts with adjacent deoxyguanosine residues on oligonucleotides, but not with single deoxyguanosine residues or any other deoxyadenosines, deoxycytosine or thymidine residues. It forms reversible intrastrand crosslinks with the GG dimer, which resembles the UV-induced dimer lesions, CPD and 6-4PP [14]. The current study indicated that acetaldehyde-treated plasmid DNA, which remained incomplete digested by restriction enzymes that recognize a GG sequence, was digested by restriction enzymes that recognize other sequences.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…The location of these tumors could reflect direct exposure to alcohol. Notably, no accumulation of somatic mutations (GG > TT) caused by acetaldehyde was observed in these tumors (data not shown). Signature 16 could be generated by direct exposure to alcohol, rather than its metabolites.…”
Section: Discussionmentioning
confidence: 87%